Dissecting ESG: Do environmental, social, and governance pillars influence share returns differently? - Wijeweera, Albert; Kortt, Michael Alexander; Kim, Namwoon (Research in international business and finance, 2026)
This study examines whether disaggregated components of Environmental, Social, and Governance (ESG) factors, namely, environmental, social, and governance scores, provide superior explanatory power in understanding share return performance compared to aggregate ESG scores. We analyse the relationship between firm size, ESG factors, and share returns by estimating augmented Capital Asset Pricing Models (CAPM) using data from 426 S&P 500 companies in 2023. Initially, a CAPM model incorporating the aggregate ESG score is estimated, followed by an extended model including disaggregated ESG components and interaction terms between ESG variables and market beta. Our findings suggest that the aggregate ESG score does not have a statistically significant direct effect on share returns. However, when disaggregated, the governance component of ESG exhibits a moderately significant negative association with share returns, implying that strong governance may reduce perceived risk, leading investors to accept lower return premiums. Although the environmental and social scores do not have a direct impact on share returns, all three ESG components exhibit significant interactions with systematic risk. This suggests that the influence of ESG on share returns arises not from the standalone ESG factors themselves, but from how these factors shape or reflect the firm’s risk environment in relation to systematic risk. In particular, environmental and governance performance scores reduce risk premiums in high-beta firms, while social performance may increase them. These results highlight the limitations of traditional asset pricing models that exclude disaggregated ESG scores and their interaction with systematic risk. The study emphasises the importance of incorporating disaggregated ESG components into multifactor investment models to more accurately capture the risk–return profile of listed firms. [Display omitted] •Does the ESG performance of publicly listed companies, as measured by the aggregated ESG score, influence share returns?•Do the disaggregated components of ESG scores provide better explanatory power compared to the aggregated ESG score?•If ESG performance affects share returns, is the impact independent of the firm’s level of systematic risk?